"Un cuarto propio" y dinero en la billetera: condiciones de producción en terapia ocupacional. - Edelvis Testa, Daniela (Brazilian Journal of Occupational Therapy / Cadernos Brasileiros de Terapia Ocupacional, 2020)
The article reflects the participation of Daniela Testa in the opening panel of the X Argentine Congress, XIII Latin American Congress of Occupational Therapy, X Meeting of Careers and Schools of Occupational Therapy of Latin America, and III Meeting of the Latin American Student Network of Occupational Therapy, held between September 23 and 27, 2019 in the city of San Miguel de Tucumán, Argentina. From the metaphor of the "room of one's own", of the English writer Virginia Woolf, we reflect on the conditions of production and dissemination of Occupational Therapy knowledge in an expanding institutional and academic context. A critical reflection is proposed on the idealized vocational profiles conceived as metaphors that attribute identities, and as veils used to hide hostile working conditions, bad payments, and/or subaltern positions. We conclude on the importance of obtaining greater equity in access to resources (material and symbolic) to increase the incidence in the professional and academic fields. The construction of a collective, plural, and diverse political subject is considered a key aspect to strengthen and expand the scope of discipline in the region.